2017
DOI: 10.1371/journal.pone.0173957
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effects of di-(2-ethylhexyl) phthalate to Eisenia fetida at enzyme, cellular and genetic levels

Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is a dominant phthalic acid ester (PAE) that has aroused public concern due to its resistance to degradation and its toxicity as an endocrine-disrupting compound. Effects of different concentrations of DEHP on Eisenia fetida in spiked natural soil have been studied in the body of the earthworm by means of soil cultivation tests 7, 14, 21 and 28 days after exposure. The results indicated that, in general, superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…This is also consistent with the ndings of Wang et al (2018) who reported an increase in MDA level and LPO propagation in the tissues of earthworms Eisenia fetida exposed to DBP. Our results are also supported by the ndings of Ma et al (2017) that reported increased MDA content in earthworms under the DEP exposure.…”
Section: Malondialdehyde (Mda/lpo) Levelsupporting
confidence: 89%
“…This is also consistent with the ndings of Wang et al (2018) who reported an increase in MDA level and LPO propagation in the tissues of earthworms Eisenia fetida exposed to DBP. Our results are also supported by the ndings of Ma et al (2017) that reported increased MDA content in earthworms under the DEP exposure.…”
Section: Malondialdehyde (Mda/lpo) Levelsupporting
confidence: 89%
“…107 Similar to the present investigation, a significant decrease in total protein was noted in E. fetida exposed to di-(2-ethylhexyl)phthalate (DEHP). 108 The significant decrease in protein content may also be due to the induction of heat shock proteins (hsps). 109 These proteins play a significant role in protein homeostasis 110 and the cellular stress response within the cell 111 and also help fish to cope with environmental changes.…”
Section: Glucose and Protein Levelmentioning
confidence: 99%
“…Di(2-ethylhexyl)phthalate (DEHP) is a typical PAE and accounts for about 50% of the global total (Ma et al, 2017). With globally increasing manufacture, the concentration of DEHP in the environment is rising gradually and has been detected in many food products, including meat, fish, cereals, vegetables, and even breast milk (Choi et al, 2014; Kappenstein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%